PENGARUH GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA DAN KINERJA DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING DI RUMAH SAKIT ISLAM LUMAJANG - Dian Kusuma Wardani; Dwi Cahyono; Toni Herlambang; Nurul Qomariah (Universitas Muhammadiyah Jember, 2017)
ABSTRACTThis study aimed to examine the effect of leadership style, on the commitment of the organization, and how dapak on job satisfaction and employee performance. Questionnaires were used to test the independent variables, the intervening variables and the dependent variable based on the researcher compiled theoretical study. Statements in the questionnaire has proven its validity. Respondents are all employees of Islamic Hospital numbering as many as 125 employees. Questionnaires were distributed to respondents as many as 125 copies and all questionnaires were returned and filled in correctly so it is worth to be processed. The results of this study indicate that the first hypothesis is that there is a positive influence between the style of leadership of the Organizational Commitment. Thus the leadership style variable test results (X1) on organizational commitment (Z) proved there is not significant positive effect between kulaitas service (X1) on organizational commitment (Z). In the second hypothesis shows that there is a positive influence between Organizational commitment and job satisfaction. Thus the test results variable organizational commitment (Z) to job satisfaction (Y1) proved no significant positive effect of organizational commitment (Z) to job satisfaction (Y1). While in the third hypothesis there is a positive relationship between leadership style on job satisfaction. Thus the results of testing leadership style variable (X) to job satisfaction (Y1) proved no significant positive effect of leadership style (X) to job satisfaction (Y1). Proof fourth hypothesis indicates that there is a positive influence between organizational commitment to employee performance. Thus the test results variable organizational commitment (Z) on the performance (Y2) proved positive influence is not significant organizational commitment (Z) on the performance (Y2). While in the fifth hypothesis that there is a positive influence among the leadership on employee performance. Thus the results of testing leadership style variable (X) on the performance (Y2) proved no significant positive influence leadership style (X) on the performance (Y2).Key Words: Leadership Style, Organizational Commitment, Job Satisfaction, Employee Performance